(untitled) - Hiismaki, Pekka (Singapore, 1997)
Modulation spectroscoy of neutrons refers to a measuring principle, characterized by classification of neutron histories in a probabilistic way, not the usual deterministic way. In order to accomplish this, neutron beams entering the sample are modulated by hightransmission, white beam selectors of the multislit type, such as Fourier or statistical choppers of highfrequency modulated spinflippers. In this scheme it is impossible to decide in a unique way through which particular slit any single neutron passed, but the distribution of histories for a large population of neutrons can nevertheless be correctly obtained, but classifying each conceivable history either as a high-probability event, based on the actual observed state of the neutron selector. So far the principle has been successfully applied to powder diffraction, but seems to offer extra degrees of freedom, if applied to measuring dispersion curves of coherent exitations, such as phonons in single crystals.
Keywords: Neutrons,Modulation spectroscopy,Nơ-tron,Nơ-tron,Điều chế quang phổ,Neutrons; Scattering,Measurement,Nhiễu xạ,Đo lường,Phân tán,Đo lường,Diffraction,Measurement